Dimensions of Transcendental Communication in the Management of Spiritual Leadership among Muslim Family Heads Practicing Shalawat - Fitriyana Fitriyana (Universitas Nurul Jadid, 2025)
Leadership within family life is closely connected to spiritual awareness, moral responsibility, and emotional stability. In Muslim communities, devotional practices often function as important sources of spiritual reflection that influence everyday attitudes and leadership behavior. However, limited research has examined how transcendental communication through religious practices shapes leadership within family contexts. This study aims to explore the dimensions of transcendental communication experienced by Muslim family heads through the practice of shalawat and to examine how these experiences contribute to the development of spiritual leadership within family life. The study employed a qualitative phenomenological approach to understand participants’ lived experiences and interpretations of shalawat as a form of spiritual communication. Data were obtained through in depth interviews with Muslim family heads who consistently practice shalawat in their daily lives. The findings reveal that the recitation of shalawat carries several interconnected meanings, including expressions of closeness to God, devotion and loyalty to the Prophet Muhammad, and the articulation of prayer and hope. These spiritual meanings contribute to emotional calmness, reinforce leadership responsibility, and encourage moral exemplarity in guiding family members. The study demonstrates that transcendental communication through shalawat functions not only as a devotional expression but also as a spiritual resource that shapes leadership attitudes and ethical awareness within family life.